(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The effectiveness of lymphotropic decongestant therapy in patients with traumatic brain injury was studied. Based on the obtained clinical and laboratory data, comparatively the main and control groups, the effectiveness of lymphotropic decongestant therapy was revealed, which prevents the progression of edema during traumatic brain injury.